Geographic Tongue and Associated Risk Factors among Iranian Dental Patients - Marieh Honarmand; Leila Farhad Mollashahi; Masomeh Shirzaiy; Marziye Sehhatpour (Tehran University of Medical Sciences, 2013)
Background: Geographic Tongue is a benign disorder involving the dorsal surface of the tongue characterized by depapillated areas with leading and folded edges in yellowish or grayish white color and sometimes with unclear borders. Many studies have reported a relationship between such condition and different risk factors. This study aimed to investigate the prevalence rate and the risk factors of geographic tongue in the patients referring to the Department of Oral Medicine of Zahedan Dental School, in 2012.Methods: Using Poisson regression model, 2000 patients referred to the Department were selected for this cross-sectional study. Data collection method included an investigation into the medical history as well as doing intraoral examinations. Using SPSS 17 software and Chi-square statistical test, the collected data were analyzed.Result: Among the 2000 patients selected, 7.8% (156 persons) suffered from geographic tongue. The results of our study show that there is a significant relationship between the occurrence of geographic tongue and a history of allergy and fissured tongue (P<0.001). There was no significant statistical relationship between the occurrence of geographic tongue and gender, smoking and medication.Conclusion: The geographic tongue is more frequently in the patients suffering from atopy or allergy as well as the patients with fissured tongue.